Ghostdance: evolving soundscapes in an immersive virtual reality experience - De Lima, Cecília (2023)
Ghostdance” is an innovative ongoing work in progress of generative art that explores the captivating blend of visual, auditory and immersive experiences in the realm of virtual reality (VR). This project harnesses the potential of generative algorithms to create a dynamic soundscape that continually transforms, inviting participants on a journey through ever-changing abstract and visual soundscapes. In the immersive VR experience, participants are transported to an environment where the auditory field evolves in real time, thanks to central generative algorithms that continually adapt and reshape the experience. Ghostdance's generative algorithms respond to the user's presence and action, detecting the properties of their movement, as defined in Laban terms. Each user embarks on a unique and unpredictable visual and auditory adventure, actively influencing the evolution of the environment through their movements and interactions in the virtual space. Ghostdance takes its name from a research project on dance in virtual reality [9]. It challenges the traditional boundaries between art forms, blurring the line between composition and improvisation. As performers move through the VR environment, they not only witness the harmonious fusion of sound and images, but also actively cocreate the evolving composition.